Little evidence of a road‐effect zone for nocturnal, flying insects. Issue 1 (27th December 2018) - Bhardwaj, Manisha; Soanes, Kylie; Lahoz‐Monfort, José J.; Lumsden, Linda F.; van der Ree, Rodney
Abstract: Roads and traffic may be contributing to global declines of insect populations. The ecological effects of roads often extend far into the surrounding habitat, over a distance known as the road‐effect zone. The quality of habitat in the road‐effect zone is generally degraded (e.g., due to edge effects, noise, light, and chemical pollution) and can be reflected in species presence, abundance, or demographic parameters. Road‐effect zones have been quantified for some vertebrate species but are yet to be quantified for insects. Investigating the road‐effect zone for insects will provide a better understanding of how roads impact ecosystems, which is particularly important given the role insects play as pollinators, predators, and prey for other species. We quantified the road‐effect zone for nocturnal flying insects along three major freeways in agricultural landscapes in southeast Australia. We collected insects using light traps at six points along 2‐km transects perpendicular to each highway ( n = 17). We sorted the samples into order, and dried and weighed each order to obtain a measure of dry biomass. Using regression models within a Bayesian framework of inference, we estimated the change in biomass of each order with distance from the road, while accounting for environmental variables such as temperature, moon phase, and vegetation structure. The biomass of nine of the ten orders sampled did not change with distance from the freeway. Orthoptera (i.e., grasshoppers and crickets) was the only order whose biomass increased with distance from the freeway. From our findings, we suggest that the impacts of roads on insects are unlikely extending into the surrounding landscape over a distance of 2 km. Therefore, if there are impacts of roads on insects, these are more likely to be concentrated at the road itself, or on finer taxonomic scales such as family or genus level. Abstract : The impacts of roads often extend into the habitat surrounding the road, reducing the occurrence of species in this area. In this study, we aimed to quantify a change in insect order biomass with distance from three major freeways in Victoria Australia. Of the ten orders sampled, Orthoptera was only order whose biomass changed with distance from highway—their biomass increased with distance from the highway.